MEMAHAMI PENGEMBANGAN TEKNOLOGI DAN PRODUK INDUSTRI PROSES DARI TAHAP RISET KE TAHAP KOMERSIAL: STUDI KASUS PENGEMBANGAN INDUSTRI FERCAF - Made Tri Ari Penia Kresnowati; Yazid Bindar (Fakultas Seni Rupa dan Desain ITB, 2021)
Technology and products are developed based on innovation, through sequential stages from basic research tocommercialization. The concept of Technology Readiness Level (TRL) defines technology development into nine stages,from idea generation (TRL 1) to the development of technology and products for commercialization (TRL 9). Leaping fromone implementation stage to another in technology development may result in technological valley of death. The processindustry is a group of industries that involve chemical processes in converting raw materials into products via series ofunit processes. Technology development for the process industry can also be defined in stages of technology readinesslevels, by using adapted specific targets for each stage. This paper presents a concept for assessing the development oftechnology for the process industry. A case study on analyzing technology readiness level for the technology developmentfor the Fercaf industry is presented along with factors involved.